Research collaboration: enhancing the research skills and self-confidence of early career academics / Faridah Mydin, Radin Siti Aishah Radin A. Rahman and Wan Muna Ruzanna Wan Mohammad - Mydin, Faridah; Radin A. Rahman, Radin Siti Aishah; Wan Mohammad, Wan Muna Ruzanna (Universiti Teknologi MARA, 2021)
An academic's career development chiefly depends on research and publication performance. For young academics, support and guidance are needed to help with the transition to new work culture and practices in the early phase of their career. This study intended to explore the benefits of research collaboration activities in relation to young academics' knowledge, skills, and personal development. A total of 15 young academics from one research university with each having less than five years of work experience selected using purposive sampling. In-depth interviews were used to collect data. The data transcribed and analyzed using thematic analysis. The findings revealed that research collaboration activities have substantial impact on young academics in updating their research knowledge and skills, and this subsequently caused them to be more confident with their ability to manage research independently. Collaboration activities also have remarkable impact on young academics' generic skills development and psychological well being, increase young academics' self-confidence, to reduce isolation as well as overcome the problem of low performance. Based on the findings, it is suggested that collaborative working culture is promoted and enhanced by universities as a practical platform for young academics to continue upgrading their knowledge and skills.